2017
DOI: 10.1371/journal.pone.0174820
|View full text |Cite
|
Sign up to set email alerts
|

The effect of meal frequency in a reduced-energy regimen on the gastrointestinal and appetite hormones in patients with type 2 diabetes: A randomised crossover study

Abstract: BackgroundAppetite and gastrointestinal hormones (GIHs) participate in energy homeostasis, feeding behavior and regulation of body weight. We demonstrated previously the superior effect of a hypocaloric diet regimen with lower meal frequency (B2) on body weight, hepatic fat content, insulin sensitivity and feelings of hunger compared to the same diet divided into six smaller meals a day (A6). Studies with isoenergetic diet regimens indicate that lower meal frequency should also have an effect on fasting and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 77 publications
2
26
0
11
Order By: Relevance
“…This is a characteristic of neuropeptides that reduce food intake, their expression is often lowered in states of negative energy balance [33]. This is also in agreement with behavioral studies previously demonstrating that fasting increases while feeding decreases the olfactory system responsiveness in rodents [36]. Furthermore, we showed that Prok2 underexpression in the MOB following Prok2 shRNA injection increased food intake with no significant repercussion on body weight.…”
Section: Discussionsupporting
confidence: 92%
“…This is a characteristic of neuropeptides that reduce food intake, their expression is often lowered in states of negative energy balance [33]. This is also in agreement with behavioral studies previously demonstrating that fasting increases while feeding decreases the olfactory system responsiveness in rodents [36]. Furthermore, we showed that Prok2 underexpression in the MOB following Prok2 shRNA injection increased food intake with no significant repercussion on body weight.…”
Section: Discussionsupporting
confidence: 92%
“…The foregut effect meant avoiding food contact with the proximal jejunum reducing the gastrointestinal secretion of anti-incretin. A hindgut effect meant that the food, which is not completely digested quickly enters the distal intestine, and stimulates the distal intestine to secrete increnin, including glucagon like peptide 1 (GLP-1), gastric inhibitory polypeptide (GIP) and peptide tyrosine-tyrosine (PYY) (20)(21)(22). This study showed that LSG could also cause a similar postoperative effect for the early response of insulin resistance as that with LGB.…”
Section: Discussionmentioning
confidence: 87%
“…An increase in the number of snacks can also increase the amount of dietary protein [54]. Data suggest that whilst there is no correlation between number of snacks and hunger [54], or at least not a positive one [55,56], there is a greater fullness-related response with higher protein intake [41,55]. Thus, when discussing meal frequency, it is essential to also consider, from an ecological perspective, that changing meal frequency could also change the percentage of energy from particular macronutrients during the day.…”
Section: Meal Frequencymentioning
confidence: 99%